2011
DOI: 10.1111/j.1365-2796.2011.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis following first-time myocardial infarction in patients with psoriasis: a Danish nationwide cohort study

Abstract: Objectives. The magnitude of cardiovascular risk associated with psoriasis has been debated and the prognostic impact of psoriasis following myocardial infarction (MI) is unknown. Therefore, we investigated the risk of mortality and adverse cardiovascular events in patients with psoriasis following first-time MI.Design, setting and participants. Cohort study of the entire Danish population including all individuals who experienced first-time MI during the period [2002][2003][2004][2005][2006]. Multivariable Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…No previous studies of post-MI prognosis in patients with IBD have been reported, but the association between IBD and worsened prognosis after MI is in line with findings in other chronic inflammatory diseases, including rheumatoid arthritis and psoriasis. 25,26 The observation of a relationship between adverse cardiovascular events and active stages of IBD further suggests that inflammation plays a central role in the association between IBD and atherothrombotic events. Indeed, the arterial and systemic immune-inflammatory processes implicated in atherosclerosis and atherothrombotic events bear many resemblances to the intestinal and systemic inflammation seen in active IBD.…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies of post-MI prognosis in patients with IBD have been reported, but the association between IBD and worsened prognosis after MI is in line with findings in other chronic inflammatory diseases, including rheumatoid arthritis and psoriasis. 25,26 The observation of a relationship between adverse cardiovascular events and active stages of IBD further suggests that inflammation plays a central role in the association between IBD and atherothrombotic events. Indeed, the arterial and systemic immune-inflammatory processes implicated in atherosclerosis and atherothrombotic events bear many resemblances to the intestinal and systemic inflammation seen in active IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system and inflammatory mechanisms, including Th1-type inflammatory responses, appear to play a role in miscarriage, suggesting that pregnancy loss could resemble an autoimmune condition 16,17 ; several autoimmune conditions (inflammatory bowel disease, psoriasis, and rheumatoid arthritis) have recently been associated with an increased risk of atherosclerosis. [18][19][20] Atherosclerotic plaques on the endothelium contain active immune cells, including activated T cells and macrophages, along with signaling molecules promoting a Th1 response 21 ; endothelial dysfunction has been associated with previous miscarriages. 5 Consequently, inflammatory processes are good candidates for underlying, Figure. Incidence rate ratios (IRRs; y axis) with 95% confidence interval for each additional miscarriage (adjusted for calendar period and number of live births) by age in years (x axis) for myocardial infarction, cerebral infarction, and renovascular hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory diseases, such as psoriasis and rheumatoid arthritis, are now known to expose patients to an increased risk of myocardial infarction and stroke. [4][5][6][7] Psoriasis is a complex multi-systemic disease influenced by environmental and genetic factors. It is characterized by expansion of Th1, Th17, and Th22 cells resulting in significant inflammation at the skin and joint levels.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Psoriasis treatments include topical corticosteroids, vitamin D analogs and phototherapy and also systemic anti-inflammatory agents, such as methotrexate, cyclosporin, or biological agents targeting tumor necrosis factor-α (TNF-α) or interleukin (IL)-12/IL-23. 8 These systemic agents all have a profound effect on skin and joint inflammation.…”
mentioning
confidence: 99%